The Role of Women in Rural Development in Bangladesh - Rashid, Sarawat; Abedin, Maupiya (Advances in Social Sciences Research Journal, 2022)
Bangladesh has significantly maintained its robust economic growth performance. According to the World Economic Forum’s Global Gender Gap Report 2022 Bangladesh is the most gender-equal country among South Asian nations. Bangladesh ranked 71st out of 146 countries on the Global Gender Gap Index 2022 with a score of 0.714. According to further information in the same report, Bangladesh has already reduced the gender gap by 72% from 2008 to 2020. Obviously the rural women have the contribution towards the development. This article is narrative reviewed by the author’s experience, existing theories, and models. Here the authors provide the information based on the reviewing concern book, scientific journal, national and international newspaper cutting as well as the concern websites. Results are based on qualitative rather than quantitative level. The paper based on the contribution of women in rural development that could be divided into the following three major categories- a) the role of women in agriculture; b) Food security; and c) The role of women in rural poverty alleviation. The paper reviled spontaneous participation of women in all developmental activities of the country is contributing to agricultural progress, food security, and assurance and poverty reduction, which is directly contributing to achieving Sustainable Development Goal one (Poverty Alleviation) and two (Hunger Free).